2022
DOI: 10.1111/bcp.15433
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric microsampling for simultaneous remote immunosuppressant and kidney function monitoring in outpatient kidney transplant recipients

Abstract: Immunosuppressant and kidney function monitoring are crucial for kidney transplant recipient follow-up. Microsamples enable remote sampling and minimise patient burden as compared to conventional venous sampling at the clinic. We developed a liquid chromatography-tandem mass spectrometry assay to quantify tacrolimus, mycophenolic acid (MPA), creatinine and iohexol in dried blood spot (DBS), and volumetric absorptive microsample (VAMS) samples. Methods:The assay was successfully validated analytically for all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 120 publications
0
29
0
Order By: Relevance
“…Some studies have reported that 24 h is a suitable time for drying a VAMS sampler under ambient conditions [ 24 , 25 ]. In our study, a reduction in the drying time to 1 h assured a high recovery of TAC, and no significant differences between the 2 h and 1 h period of VAMS drying were observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have reported that 24 h is a suitable time for drying a VAMS sampler under ambient conditions [ 24 , 25 ]. In our study, a reduction in the drying time to 1 h assured a high recovery of TAC, and no significant differences between the 2 h and 1 h period of VAMS drying were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Protti et al concluded that IS should be added immediately during the analytical process [ 29 ]. In most published studies, IS was added to the solution for analyte extraction from VAMS [ 24 , 25 , 26 , 29 , 30 , 31 , 32 , 33 ]. In a survey by Kita et al [ 27 ], ASC was added after extraction from the VAMS tip, similar to our LC-MS/MS method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…111 Microsampling has been extensively studied for the determination of tacrolimus and mycophenolic acid, two of the most commonly prescribed IMS used to prevent organ rejection in recipients of solid organ transplants. 32,63,64,112,113 samples due to poor sample quality) and costs (7 times lower than Mitra device). 32,64 Additionally, use of non-contact Hct prediction strategies such as NIR and UV/VIS spectroscopy coupled to an automated DBS workflow was found to adequately correct for Hct effect in determining IMS concentrations.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%